2022
DOI: 10.3389/fgene.2022.872056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Pathogenic Variants on Phenotypes of Familial Hypercholesterolemia

Abstract: Objective: It has been shown that pathogenic variants are associated with poor clinical outcomes in patients with familial hypercholesterolemia (FH). However, data on the effect of different types of pathogenic variants on FH phenotype is limited.Methods: We retrospectively investigated the associations between genotypes and phenotypes, including low-density lipoprotein (LDL) cholesterol level and the occurrence of major adverse cardiac events (MACEs), defined as cardiovascular death, myocardial infarction, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is also noteworthy that almost half of our study subjects had nonsense mutation in LDLR , which we believe are associated with severe form of FH. In fact, we have shown that phenotype of FH with nonsense mutation in LDLR is severer than that of FH with missense mutation [20] .…”
Section: Discussionmentioning
confidence: 80%
“…It is also noteworthy that almost half of our study subjects had nonsense mutation in LDLR , which we believe are associated with severe form of FH. In fact, we have shown that phenotype of FH with nonsense mutation in LDLR is severer than that of FH with missense mutation [20] .…”
Section: Discussionmentioning
confidence: 80%
“…The greater the effect on lifetime LDL-C, the greater the effect on risk independent of observed LDL-C. For example, when considering specific types of FH variants, loss-of-function variants of LDLR are associated with higher LDL-C compared to other FH variants. Likewise, such variants have been found to associate with greater atherosclerotic risk independent of baseline LDL-C compared to other variant types [37 ▪ ,38 ▪ ]. This greater magnitude of independent risk seen among carriers of LDLR null variants reflects a greater impact on lifetime LDL-C compared to other variant types.…”
Section: Mainmentioning
confidence: 97%
“…Genotype–phenotype correlations exist in some diseases and genes [ 29 ], such as in FH. For example, the phenotype of FH caused by nonsense variants in the LDLR is much worse than that caused by missense variants [ 30 ]. Another association study revealed that the effect size for “FH-variant” coronary artery disease was inversely associated with their allele frequency [ 31 ], which is in accordance with the concept that rarer genetic variants tend to have larger effect sizes on diseases [ 32 ].…”
Section: Genotype–phenotype Correlations Between Fh and Homozygous Fhmentioning
confidence: 99%
“…In addition to the presence of FH variants, the type of pathogenic variants as well as other genetic situations, including polygenic risk scores comprising common genetic variations, are all associated with the phenotype [ 44 ]. We have shown that patients with FH caused by a protein-truncating variant had poorer prognosis than patients with FH caused by a missense variant ( Figure 3 ) [ 30 ]. Accordingly, genetic backgrounds need to be considered during risk assessment in patients with FH [ 45 ].…”
Section: Factors Associated With Fh Prognosismentioning
confidence: 99%
See 1 more Smart Citation